Scientific and methodological aspects of the choice of discount rate in the evaluation of investment projects - Sorokina, L.; Hoiko, A. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the issues of evaluating the efficiency of investment projects, taking into account the justified and objective choice of the discount rate, which significantly affects the accuracy of the indicators of the economic efficiency of the evaluated investment project. In the conditions of an acute shortage of investment resources, the desire to increase the accuracy of the predictive assessment of the effectiveness of investment projects necessitates the search for new scientific and methodological approaches to the justified choice of the discount rate. In each specific situation, this choice depends on a large number of different factors, which are conditionally divided into two groups - internal and external. Unfortunately, in investment projects developed by Ukrainian enterprises, insufficient attention is paid to justifying the discount rate. The article provides an analysis of the main methods of determining the value of the discount rate when evaluating investment projects and scientific and methodological approaches to the selection of the discount rate in order to increase the objectivity of the predictive assessment of the feasibility of implementing an investment project. The essence of the advantages and disadvantages of such "traditional" methods of determining the discount rate of investment projects, such as the SARM model, the cumulative construction model, and the WASS model, are revealed. The effect of the intensity of exogenous factors in the form of the cost of credit resources, tax rates, inflation rates on the result of the assessment of the efficiency of the investment project has been specified. The main problems of justifying the economic efficiency of investment projects in the post-war recovery of the national economy are formulated. The author’s rationale for the cumulative premium to the discount rate is given, due to the risk of speculative growth in the cost of construction caused by excess demand for construction work. The indicator of the expected duration of the portfolio of all orders of the construction enterprise, expressed in months, is proposed for use. On the basis of a cluster analysis of retrospective data, the linguistic terms of this meaning "deficit of orders", "partial..." and "sufficient security of the medium-term portfolio of orders" and their corresponding Gaussian membership functions are substantiated. An artificial intelligence system has been developed for forecasting the most likely percentage of speculative overestimation of the cost of construction works performed by the contractor, and the feasibility of using the output of this system as a cumulative premium to the discount rate has been proven.